Teaching Children To Save On The Natural Environment During Class Hours - Kutlimuratova Namunaxon Aqilbek qizi; Xudayberdiyeva Dilafruz Abidovna (Euro Asian Journal Publishing, 2024)
The most important condition for the successful implementation of an integrated approach is the creation of an environment in which adults demonstrate to children by personal example the right attitude to nature and actively, to the extent possible, participate together with children in environmental activities
Keywords: nature; save nature; thrift; environmental activities